Are There Cultural Effects on Saving? Some Cross-Sectional Evidence - Carroll, C. D.; Rhee, B.-K.; Rhee, C. (Quarterly Journal of Economics, 1994)
Why are there such large differences in saving rates across countries? Conventional economic analyses have not been successful in explaining international saving differences, so economists have sometimes suggested that national saving differences may be explained by cultural differences. This paper tests the hypothesis that cultural factors influence saving by comparing saving patterns of immigrants to Canada from different cultures. Using data from the Canadian Survey of Family Expenditures, we find no evidence of cultural effects on saving.